Islamisasi Ilmu Pengetahuan Menurut Ismail Raji al-Faruqi - Daulay, M Ilham; Maraimbang, Maraimbang; Junaidi, Junaidi (Asian Journal of Islamic Studies and Da'wah, 2024)
Ismail Raji Al-Faruqi is a muslim scholar who tried to integrate science with religion whose work is known as “Islamization of Science” based on monotheism which is the foundation of Islamic teachings. Where religion is needed in studying classical Islamic scholarship and modern Western science which is then processed into scientific knowledge. The findings of the debate on the Islamization of science, as reported by Ismail Raji Al-Faruqi, are covered in this study. The methodology used in this study is content analysis, or philosophical analysis, which analyzes data using reasoning, introspection, and argumentation. In order for scholars to determine how Ismail Raji Al-Faruqi, in his prime, defined the Islamization of science. Ismail Raji al-Faruqi is a notable thinker whose ideas have the power to lift the Muslim community's intellectual consciousness and act as a light in the face of darkness in the contemporary world. Numerous publications, including one in Indonesian, have been translated from Ismail Raji Al-Faruqi's numerous writings. Books like Tauhid, Art of Tauhid, Atlas of Islamic Culture, and others have been translated.